Integrating Problem-Based Learning with Ulul Albab Values to Enhance Cognitive and Character Outcomes in Introductory Accounting: A Mixed-Methods Study - Karim Amrullah, Abdul Malik; Kholilah, Kholilah; Wahidmurni, Wahidmurni; Putri, Sheila Febriani (Global Educational Research Review, 2025)
Purpose –  This study tests whether Problem-Based Learning integrated with Ulul Albab values (PBL-UA) improves cognitive attainment in Introductory Accounting 2 and explicates how character values are internalized across PBL cycles—evidence relevant to Indonesia’s human-capital agenda toward Golden Indonesia 2045. Methods/Design/Approach – Sequential explanatory mixed-methods (QUAN→qual) with a quasi-experimental, non-equivalent control pretest–posttest in two intact classes at UIN Maulana Malik Ibrahim (n = 52; 26/26). The experimental class completed five PBL cycles over eight meetings using MSME rading-company cases; the control received conventional instruction. Cognitive performance came from an authentic accounting-cycle task scored by two independent raters (analytic rubric). Assumptions were checked; an independent-samples t-test examined group differences. Qualitative data (artifacts, reflections, interviews) were analyzed via directed content analysis aligned to the four Ulul Albab pillars and integrated through joint displays.. Findings – The experimental class outperformed the control on the posttest (M = 83.65 vs 76.42; mean difference = 7.23). The t-test indicated a significant advantage for PBL-UA with assumptions satisfied (Shapiro–Wilk p > .05; Levene’s F = 3.415, p = .071). Qualitative evidence showed consistent internalization of discipline, cooperation, ethical accountability in recording “every rupiah,” communication ethics, tolerance, emotion regulation, and reflective decision-making across the five cycles. Originality/Value – Adds comparative evidence in Indonesian accounting education and explicates a value → process → artifact → outcome mechanism linking Ulul Albab to attainment; findings are bounded by non-random class assignment ad online delivery during the pandemic. Practical Implications – Adopt five-cycle PBL with MSME cases, analytic rubrics and staged feedback, just-in-time Excel micro-tutorials (e.g., SUMIF, VLOOKUP), rotating roles with equitable presentations, and simple spreadsheet audit trails to strengthen accountability and accuracy. Keywords Problem-based learning, accounting education, cognitive achievement, ulul albab, mixed-methods. Paper type Research paper